Metals, the plasma of the poor man? - Rolfs, C. (HNPS Advances in Nuclear Physics, 2021)
The electron screening effect in the d(d,p)t reaction has been studied for deuterated metals, insulators, and semiconductors, i.e. 58 samples in total. As compared to measurements performed with a gaseous D2 target, a large effect has been observed in most metals, while a small (gaseous) effect is found e.g. for the insulators, semiconductors, and lanthanides. The periodic table provides the ordering of the observed small and large effects in the samples. An explanation of the large effects in metals is possibly provided by the classical plasma screening of Debye applied to the quasi-free metallic electrons. The data also provide information on the solubility of hydrogen in the samples.